1. Rewrite one side (or both) by combining like terms. Option C
2. Yes, the equations are equivalent. Option A
1.
Equation A ; 2x -1 = 5x
Equation B ; -1 = 3x
To get equation B from equation A
2x - 1 = 5x
Collect like terms
-1 = 5x -2x
Subtract the like terms
-1 = 3x
Thus, rewrite one side (or both) by combining like terms. Option C
2. 2x - 1 = 5x ...... equation A
Solution ;
2x -5x = 1
-3x = 1
x = -1/3
-1 = 3x
Solution;
x = -1/3
Thus, the equations are equivalent. Option A
Learn more about algebraic expressions here:
https://brainly.com/question/4541471
#SPJ1